(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article highlights the immense importance of fostering interest in reading books, which plays a crucial role in enhancing the spiritual and intellectual potential, consciousness, and worldview of our people, especially the younger generation. It emphasizes the significance of cultivating a well-rounded individual who lives with love and loyalty for their motherland and people.